Herbert Spencer lectures: Decennial issue, 1905-1914 (Clarendon Press, 1916)
1905. Herbert Spencer, by Frederic Harrison.--1906. The Voluntaryist creed, by Auberon Herbert.--1907. Probability, the foundation of eugenics, by Francis Galton.--1908. Individualism and after, by Benjamin Kidd.--1909. Herbert Spencer and animal evolution, by Gilbert Charles Bourne.--1910. Evolution-Darwinian and Spencerian, by Raphael Meldola.--1911. Biological fact and structure of society, by W. Bateson.--1912. On Aristotle as a biologist, by D'Arcy Wentworth Thompson.--1913. Spencer's philosophy of science, by C. Lloyd Morgan.--1914. Scientific method in philosophy, by the Hon. Bertrand Russell.